A qualitative investigation of crisis cafés in England: their role, implementation, and accessibility - Heather Staples; Gianna Cadorna; Patrick Nyikavaranda; Lucy Maconick; Brynmor Lloyd-Evans; Sonia Johnson (BMC, 2024)
Abstract Background Crisis cafés (also known as crisis sanctuaries or havens) are community-based services which support people in mental health crises, aiming to provide an informal, non-clinical and accessible setting. This model is increasingly popular in the UK; however, we are aware of no peer-reviewed literature focused on this model. We aimed to investigate the aims of crisis cafés, how they operate in practice and the factors that affect access to these services and implementation of the intended model. Methods A qualitative approach was used. Semi-structured interviews were conducted with 12 managers of crisis cafés across England. These interviews explored managers' views on the implementation of their services, and the factors that help and hinder successful implementation. Data were analysed using Braun and Clarke's reflexive thematic approach. Results We identified five main perceived aims for crisis cafés: providing an alternative to Emergency Departments; improving access to crisis care; providing people in acute distress with someone to talk to in a safe and comfortable space; triaging effectively; and improving crisis planning and people's coping skills. Factors seen as influencing the effectiveness of crisis cafés included accessibility, being able to deliver person-centred care, relationships with other services, and staffing. These factors could both help and hinder access to care and the implementation of the intended model. There were a number of trade-offs that services had to consider when designing and running a crisis café: (1) Balancing an open-door policy with managing demand for the service through referral routes, (2) Balancing risk management procedures with the remit of offering a non-clinical environment and (3) Increasing awareness of the service in the community whilst avoiding stigmatising perceptions of it. Conclusions Findings illustrate the aims of the crisis café model of care and factors which are influential in its implementation in current practice. Future research is needed to evaluate the efficacy of these services in relation to their aims. Crisis café service users' views, and views of stakeholders from the wider crisis care system should also be ascertained.